Improved measurement of ultrasound a-mode velocity for use in b-mode images for measurement of fat using image segmentation technique / Muhamad Hazwan Abdul Halim - Abdul Halim, Muhamad Hazwan (2015)
Fat measurement is one of the methods used in meat quality assessments. The need to perform the assessment non-invasively motivates researchers to study the non-invasive methods for fat measurement. For that purpose, ultrasound has the best prospect due to its non-invasive, time saving and relatively low-cost advantages. The improvement in ultrasound method for fat measurement is not only on the advancement of the ultrasound equipment but also the accuracy of data analysis. Two current issues that have arisen are the influence of protective layer on the accuracy of ultrasonic velocity measurement using A-mode analysis and the B-mode image positioning accuracy due to the application of the predetermined ultrasonic velocity in B-mode imaging. This research implemented new approach in performing the measurement of ultrasonic velocity and ultrasound B-mode analysis. To increase the accuracy of ultrasonic velocity measurement, the thickness of the protective layer was first determined used in ultrasonic velocity measurement. To increase the positioning accuracy of B-mode image, the actual determined velocity was used rather than the predetermined velocity. The improvements made were successful in increasing the accuracy of the ultrasonic velocity measurement and the positioning of the B - mode image. Subsequently, this method was then used to measure intramuscular fat content in chicken fillet. Better correlations between the ultrasound properties (velocity, image histogram mean and percentages of fat pixel) and percentage of fat content measured by Soxhlet Method were observed in the improved method. In the conclusion, the accuracy of ultrasound fat measurement improved with the improvement made on ultrasonic velocity measurement used in adapted B-mode imaging.